"Heave Half a Brick at Him": Hate Crimes and Discrimination against Muslim Converts in Late Victorian Liverpool. Issue 1 (2nd January 2017) - Singleton, Brent
Abstract: Throughout the existence of the Liverpool Moslem Institute, 1887–1908, there were many incidents of discrimination, intimidation, violence, and other acts of hate directed toward the British converts to Islam. This was particularly evident during the first decade after the group's founding. The band of Muslims, led by Sheik Abdullah William Henry Quilliam, faced continued opposition, be it disruptions of events and religious services, or violent street fighting. This article explores the incidents of hate and discrimination, the milieu in which they occurred, and the reaction of the Muslim community. A brief comparison to the experience of the contemporaneous American Muslim converts also is presented.